Values of character education in the Opera Kecoa drama script by N. Riantiarno - Agung Prayitno Putro; Herman J Waluyo; Nugraheni Eko Wardhani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2017)
This study aims to describe the values of character education contained in a drama script. This research uses descriptive qualitative method with the subject of research is drama Opera Kecoa by N. Riantiarno. Data sources are obtained from places and events, informants, drama script, and documents. Data collection using document analysis techniques. As one form of literary work, Opera Kecoa drama script contains character education values. The values of character education in this drama script are shown through characterizations and the flow of events in each round. Based on the results of the analysis found ten character education values contained in the Oera Kecoa drama script, these values include: religious, social care, tolerance, hard work, discipline, democracy, patriotic, love peace, friendly, independent, creative, and responsibility . By reason of the values of these characters, the Opera Kecoa drama script, can be used as a medium of learning in the college literature.